Magnetically controlled exchange process in an ultracold atom-dimer mixture - Knoop, Steven; Ferlaino, F.; Berninger, M.; Mark, M.; Nägerl, H.-C.; Grimm, R.; D’Incao, J. P.; Esry, B. D. (Physical review letters, 2010)
We report on the observation of an elementary exchange process in an optically trapped ultracold sample of atoms and Feshbach molecules. We can magnetically control the energetic nature of the process and tune it from endoergic to exoergic, enabling the observation of a pronounced threshold behavior. In contrast to relaxation to more deeply bound molecular states, the exchange process does not lead to trap loss. We find excellent agreement between our experimental observations and calculations based on the solutions of three-body Schrödinger equation in the adiabatic hyperspherical representation. The high efficiency of the exchange process is explained by the halo character of both the initial and final molecular states.